2019
DOI: 10.1093/jisesa/iez110
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Field-Collected Spodoptera frugiperda (Lepidoptera: Noctuidae) Strains Exposed to Different Transgenic and Refuge Maize Hybrids in Argentina

Abstract: Spodoptera frugiperda (J. E. Smith) is one of the major pests of maize in Argentina. The main tool for its control is the use of genetically modified maize hybrids expressing Bacillus thuringiensis (Bt) insecticidal proteins. Maize growers in Argentina initially controlled this pest with Bt maize that expressed a single Bt protein (Cry1Ab or Cry1F). Currently it is necessary to plant maize cultivars that produce two Bt proteins to achieve the satisfactory control. Recently, Cry1F field-evolved resistant popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The use of chemical insecticides is the most effective approach for the control of FAW (Belay et al 2012). However, the pest was reported to develop resistance against major classes of commonly used insecticides (Zhu et al 2015) and Cry proteins of Bacillus thuringiensis Berliner (Bacillaceae) as well (Murúa et al 2019); therefore, safer, eco-friendly control strategies need to be developed and further implemented. Biological control offers a promising strategy against a wide range of insect pests, and biopesticides being environmentally safer are potential alternatives to chemical pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…The use of chemical insecticides is the most effective approach for the control of FAW (Belay et al 2012). However, the pest was reported to develop resistance against major classes of commonly used insecticides (Zhu et al 2015) and Cry proteins of Bacillus thuringiensis Berliner (Bacillaceae) as well (Murúa et al 2019); therefore, safer, eco-friendly control strategies need to be developed and further implemented. Biological control offers a promising strategy against a wide range of insect pests, and biopesticides being environmentally safer are potential alternatives to chemical pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…This proves its efficiency in controlling even larger insects that may have migrated from ruzigrass plants and making it possible to recommend intercropping with this forage plant as an alternative refuge. Although there are already FAW populations that are resistant to Bt technology, 32,33,[69][70][71] transgenic corns that express the Vip3Aa20 protein in combination with other proteins still demonstrate synergism and a high control efficiency. [72][73][74] These cause high levels of mortality in susceptible and heterozygous larvae, even when initially fed with non-Bt corn for a period of 10 days, 65 and have a high effectiveness in the field.…”
Section: Discussionmentioning
confidence: 99%
“…26,29 In this way, exposure to toxins for a short period allows the survival of these insects, favoring resistance evolution. 30 In Brazil and other countries of the American continent, the existence of FAW population that is resistant to Bt toxins, such as Cry1Ab, 31 Cry1F, 32,33 and Cry2Ab2, 34,35 has already been documented. For the time being, the protein Vip3Aa20 remains effective in controlling this pest under field conditions, 36,37 but it urgently needs to be conserved through good management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent research on fall armyworm larvae collected from Bt transgenic maize fields and reserves confirmed a considerable decrease in the efficiency of Cry1F and showed an absence of efficiency in Cry-1Ab (Murúa et al, 2019).…”
Section: Resistancementioning
confidence: 98%